The Effect of Health Education to The Active Presence of Mother to Take Their Toddlers to Posyandu - Maria Ulfa; Laily Prima Monica (Journal of Ners and Midwifery, 2021)
The decrease of the active presence of toddlers at the posyandu has become a problem for health workers in monitoring the health and development of infants and toddlers in their working areas. This is due to several reasons, one of which is from the mothers who are lazy and do not know what is the benefits they will get when they are taken to the posyandu. The purpose of this study was to determine the effect of health education to the active presence of mothers to take their toddlers to posyandu. Methods: This study used a "Pre-Experimental" design. The sample was 30 respondents taken by using purposive sampling technique. The independent variable was health education and the dependent variable was active presence of mother to take their toddler to posyandu. The instrument used health education materials and observations on the respondent's attendance book in the last 8 months. Result: the sattistical Wilcoxon rankTest showed p value = 0.05. This meant that health education affected the active presence of mothers in bringing their toddlers to join the posyandu at Polindes Semen, Gandusari District. Based on the result, it is expected to all mothers to be active in joining Posyandu so that they can get education on how to stimulate and check their children's growth and development. For health workers, the results of this study can be used as an input so that they can improve the provision of counseling during posyandu activities and the target of achieving the presence of infants and toddlers in the areas can be achieved.